Regulatory CD4+ T cells redirected against pathogenic CD8+ T cells protect NOD mice from development of autoimmune diabetes - Kakabadse, Dimitri; Chen, Dawei; Fishman, Sigal; Weinstein-Marom, Hadas; Davies, Joanne; Wen, Li; Gross, Gideon; Wong, F. Susan (Frontiers in Immunology, 2024)
Introduction: In this study, we report a novel therapeutic approach redirecting antigen-specific CD4 + T cells recognising a hybrid insulin peptide (BDC2.5 T cell receptor (TCR) transgenic CD4 + T cells) to attract and suppress islet-specific CD8 + T cells T cells in the non-obese diabetic (NOD) mouse model, and prevent the development of autoimmune diabetes. Methods: Purified BDC2.5 CD4 + T cells were induced to differentiate into regulatory T cells (Tregs). The Tregs were then electroporated with mRNA encoding chimeric human 2 microglobulin (hβ2m) covalently linked to insulin B chain amino acids 15-23 (designated INS-eTreg) or islet-specific glucose-6-phosphatase related protein (IGRP) peptide 206-214 (designated IGRP-eTreg). Immunoregulatory functions of these engineered regulatory T cells (eTregs) were tested by in vitro assays and in vivo co-transfer experiments with β-cell-antigenspecific CD8 + T cells in NOD.Scid mice or by adoptive transfer into young, pre-diabetic NOD mice. Results: These eTregs were phenotyped by flow cytometry, and shown to have high expression of FoxP3, as well as other markers of Treg function, including IL-10. They suppressed polyclonal CD4 + T cells and antigen-specific CD8 + T cells (recognising insulin or IGRP), decreasing proliferation and increasing exhaustion and regulatory markers in vitro. In vivo, eTregs reduced diabetes development in co-transfer experiments with pathogenic antigen-specific CD8 + T cells (INS-CD8 + or IGRP-CD8 + cells) into NOD.Scid mice. Finally, when the eTreg were injected into young NOD mice, they reduced insulitis and prevented spontaneous diabetes in the recipient mice. Conclusion: Our results suggest a novel therapeutic strategy to protect NOD mice by targeting antigen-specific cytotoxic CD8 + T cells, using redirected antigen-specific CD4 + Treg cells, to suppress autoimmune diabetes. This may suggest an innovative therapy for protection of people at risk of development of type 1 diabetes.